“A FIRE DON’T BURN UNLESS IT’S STARTED”: PRINCE’S PROVERBIAL LYRICS - Williams, Derek (Proverbium - Yearbook, 2024)
This article explores the use of proverbial language in songs by the late rhythm and blues and rock music artist, Prince. This article uses a selective array of the songs in which Prince used proverbs, proverbial sayings, and proverbial expressions during the time frame that spans from his first release, For You (1978), through his last release before his death in April 2016, HITNRUN Phase Two (2016). Using Sw. Anand Prahlad’s grammatical and situational categories of meaning as primary tools for the discussion, the author interprets the meaning of Prince’s proverbial language in the larger context of three “masks” or personae that the artist adopted during his long career (The International Lover, Goldnigga, and The Purple Yoda). Finally, the article compares Prince’s proverbial output in song to those of known proverb users in literature.